The economic and social effects of the EU Free Trade Agreement with Vietnam - Jan Grumiller; Werner G. Raza; Cornelia Staritz; Bernhard Tröster; Rudi von Arnim; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2018)
The EU has recently concluded or is currently in the process of negotiating a number of bilateral free trade agreements with both industrialized countries, e.g. Japan, and developing as well as emerging economies. Negotiations with the latter group also include Vietnam, where negotiations were formally concluded in December 2015. After completing the legal review of the text of the agreement, which is underway at the time of finalizing this report (July 2018), the agreement will then submitted to the Council of Ministers for approval. Based on the EU trade strategy "Trade for All. Towards a more responsible trade and investment policy", published in October 2015, these so-called new generation bilateral trade agreements are deliberately designed as 'deep and comprehensive". In other words, while also targeting remaining traditional trade barriers, such as tariffs and quotas, above all they aim at tackling non-tariff measures that are deemed relevant for trade. As is also stressed by the EC, trade liberalization in the extended definition of the new EU trade agenda must promote sustainable development both in the EU and the partner countries, i.e. economic growth that is socially inclusive and respects ecological boundaries. In other words, adherence to the principle of policy coherence for sustainable development (PCSD), as recently defined by the UN Agenda 2030 for Sustainable Development and subsequently adopted by the new European Consensus on Development, is required. New generation FTAs are therefore primarily to be assessed against this yardstick, which is the approach adopted in this study with respect to the EU FTA with Tunisia (DCFTA). The report assesses the EVFTA between the EU and Vietnam. The report starts with an economic overview and an analysis of the trade patterns between the EU and Vietnam (Section 2). In section 3, the key contents of the EVFTA are assessed. This includes a detailed analysis of the market access offer and other key issues, as well as a discussion of the trade and sustainable development aspects of the respective agreement, and finally of EU development cooperation in the partner country. Section 4 analyzes the economic implications of the EVFTA on Vietnam. The section starts with an assessment of the economic impacts of the agreement, based on simulations with the ÖFSE Global Trade Model. Based on interviews with stakeholders and field research in the partner country, negotiating concerns and implementation challenges associated with the agreement are detailed in the subsequent section. Further, sectoral case studies are analyzed in order to investigate the potential of the EVFTA on the export side, highlighting the opportunities and challenges for export promotion policies in the context of global value chains and related lead firm strategies as well as local competitiveness conditions. The sectoral case studies focus on the textile and apparel sector and the aquaculture sector with a focus on pangasius fish and shrimp. Section 5 provides a summary of the main findings with respect to economic impacts, the sectoral case studies and the sustainability concerns. Upon that basis, key policy recommendations are proposed in the areas of adjustment assistance and productive development promotion.
Additional information: Final report, 12 July 2018
Keywords: 330; Freihandelsabkommen; Wirkungsanalyse; Soziale Folgen; Vietnam; EU-Staaten